MITIGASI BENCANA MELALUI PENGURANGAN RISIKO BENCANA TERHADAP KEMAMPUAN TANGGAP DARURAT BENCANA BANJIR - sari, Shinta wisma (NHM PRESS, 2023)
Low preparedness can lead to more serious disaster impacts (floods), namely the number of fatalities, serious injuries, the number of refugees and the occurrence of diseases due to poor environmental conditions. (Kusno F., 2019). The research aims to Improve Disaster Mitigation through Disaster Risk Reduction (DRR) Strategies for Flood Disaster Response. Mitigation Activities through Disaster Risk Reduction (DRR) include Disaster Risk Assessment Methods, Seasonal Calendar Analysis, and Table Top Applications. By knowing the degree of vulnerability and hazard and the amount of capacity they have, the community is able to plan anticipatory actions to be taken. Strategies that can be carried out to reduce disaster risk including several activities aimed at creating resilience in society against the consequences of natural, technological and environmental disasters and improving the disaster defense model into disaster impact management by incorporating risk prevention strategies into activities sustainable development.